2007
DOI: 10.1210/jc.2006-2513
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor-Interacting Protein Gene Mutations in Familial Isolated Pituitary Adenomas: Analysis in 73 Families

Abstract: AIP mutations, of which nine new mutations have been described here, occur in approximately 15% of FIPA families. Although pituitary tumors occurring in association with AIP mutations are predominantly somatotropinomas, other tumor types are also seen. Further study of the impact of AIP mutations on protein expression and activity is necessary to elucidate their role in pituitary tumorigenesis in FIPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
249
0
14

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 289 publications
(274 citation statements)
references
References 22 publications
11
249
0
14
Order By: Relevance
“…Despite the MEN1-like features of the patients described, studies from Ozawa and colleagues at the NIH and from (24). Despite the advent of mutations in AIP as potential causative features in IFS, the genetic pathophysiology of IFS remains to be fully described as we have found that in 50% of IFS families, no AIP mutations exist (25).…”
Section: Men1mentioning
confidence: 77%
See 3 more Smart Citations
“…Despite the MEN1-like features of the patients described, studies from Ozawa and colleagues at the NIH and from (24). Despite the advent of mutations in AIP as potential causative features in IFS, the genetic pathophysiology of IFS remains to be fully described as we have found that in 50% of IFS families, no AIP mutations exist (25).…”
Section: Men1mentioning
confidence: 77%
“…Among the FIPA cohort, families with two, three, and four affected members are seen (18,25). FIPA is characterized by a predominance of prolactinomas and GH-secreting tumors, which account for about 75% of the cohort (Fig.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Familial syndromes associated with GH hypersecretion include multiple endocrine neoplasia type 1 (MEN1), in which pituitary, parathyroid, and pancreatic tumors might be associated (4), and the similar MEN4 syndrome caused by germline mutations in the CDKN1B/p27 gene; McCune-Albright syndrome, which involves polyostotic fibrous dysplasia and cutaneous pigmentation (5); and Carney complex, whose clinical picture includes skin pigmentation, mucocutaneous myxomatosis, cardiac myxoma, thyroid and breast lesions (6). Isolated familial acromegaly is described with loss of heterozygosity in chromosome 11q13 (7) and, recently, low-penetrance germline mutations in the aryl hydrocarbon receptor-interacting protein (AIP) gene that were found in individuals who had familial pituitary isolated adenoma (FIPA) predisposition (8)(9)(10).…”
mentioning
confidence: 99%